PENGARUH SARANA DAN PRASARANA TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR DAN PERMASALAHANNYA - Rizki Ananda; Nursantri Muslimah; Izra Aulia Rahma; Emeliani Rahmatullah; Farah Zhefira Andina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Using a qualitative methodology based on secondary data, this study aims to analyze the effect of facilities and infrastructure on student learning achievement in primary schools. Data collected from various sources, including scientific journals, research reports, government regulations and relevant academic literature, focuses on further understanding how limited educational facilities, which include libraries, textbooks, classrooms, teaching aids and learning media, can affect student motivation and learning outcomes, particularly in primary schools in remote areas. The analysis shows that inadequate facilities and infrastructure affect the effectiveness of the teaching-learning process and students' academic development. Therefore, the improvement and equality of education facilities is an important action that should be prioritized by the government and all education stakeholders.